Pengaruh Variasi Jumlah Sudu Dan Jarak Sudu Dengan Saluran Keluar Terhadap Daya Output Listrik Turbin Vortex - Yusron Nur Faizal; Danar Susilo Wijayanto; Yuyun Estriyanto (Nozel : Jurnal Pendididikan Teknik Mesin, 2022)
Hydroelectric power is one of the options in utilizing renewable energy. The generators that are made usually use waterfalls. Low water flows such as rivers have not been utilized optimally. This becomes a reference for utilizing river flow by turning it into a whirlpool or vortex flow. This study analyzes the effect of variations in the number of blades and the distance between the blades and the outlet on the electrical output power of a vortex type water turbine. The research method used is experimental. The independent variables are variations in the number of blades 2, 3, and 4 and variations in the distance between the blades and the outlet 4 cm, 6 cm, 8 cm, and 10 cm. The dependent variable of the research is the output power and efficiency of the vortex type water turbine. Data analysis techniques using quantitative descriptive analysis techniques. The results showed that the maximum data for calculating the electrical output power and efficiency with a water discharge of 6.34 L/s was obtained at the number of blades 4 and the distance between the blades and the outlet 6 cm, namely 9.72 Watt and 65.77%. Based on these results indicate that the more the number of blades, the higher the electrical output power produced. Meanwhile, the variation of the distance between the blade and the outlet increases at a height of 6 cm and relatively decreases at a height of 8 cm and 10 cm.